EFFECT OF DRILL PASSING PRACTICE ON THE LEVEL OF PASSING ACCURACY IN FUTSAL GAMES OF FUTSAL EXTRACURRICULAR PARTICIPANTS SMP NEGERI 2 SUNGGUMINASA - Malik, Farid Giffari; Badaru, Benny; Arimbi, Arimbi; Hudain, Muh. Adnan; Sudirman, Sudirman (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to determine the effect of passing drill training on the level of passing accuracy in futsal games. This research is a type of experimental research. The population of this study were extracurricular futsal students of SMP Negeri 2 Sungguminasa with a total research sample of 25 athletes using the total sampling method. The data analysis technique used is descriptive analysis technique using Analysis Of Variance (ANOVA) with a significant level of 0.05. The results showed that the effect of passing drill training on the passing accuracy of extracurricular students of SMP Negeri 2 Sungguminasa had an influence with a significant value of 0.000 and a tcount value of -17.321. The conclusion is that the drill training method can have a significant effect on the passing ability of futsal extracurricular participants at SMP Negeri 2 Sungguminasa.